Manifestation of Histoplasmosis in the oral cavity: case report (Research, Society and Development, 2020)
Background: Histoplasmosis is a systemic fungal infection caused by the dimorphic fungus Histoplasma Capsulatum which has spores in soils, mainly acids, in endemic areas. Clinical manifestations are associated with immunocompetence and present signs and symptoms that include: fever, weakness, weight loss, respiratory signs, hepatosplenomegaly, superficial lymphadenopathies. Oral manifestations are secondary in immunocompetent patients, but in immunosuppressed patients, especially those infected with HIV, the disease becomes symptomatic in 95% of cases where the CD4 count is less than 200/mm³. Oral symptoms present as everted edge ulcerative lesion, nodules or even vegetative lesions which, although rare, deserve careful observation to be early diagnosed and treated to avoid systemic complications. Objective and Case Report: The objective of this work is to report the diagnosis of the oral manifestation of Histoplasmosis, in an immunosuppressed patient, with an ulcerative lesion in the upper lip with characteristics of malignancy. Conclusion: The isolated oral manifestations of Histoplasmosis make the diagnosis more difficult due to its rarity, within this context, it is essential to know the oral manifestations of Histoplasmosis, especially in immunocompromised patients, who are more susceptible to opportunistic infections.